Diseminasi Modul Ajar Pembelajaran Berdeferensiasi berbasis STEM di SMA Asparaga Gorontalo - Tahir, Wawan; La Kilo, Akram; Salimi, Yuszda K.; Laliyo, Lukman A.R. (Universitas Negeri Gorontalo, 2024)
DISSEMINATION OF STEM-BASED DIFFERENTIATED TEACHING MODULE AT ASPARAGA SENIOR HIGH SCHOOL IN GORONTALO. This study disseminates differentiated STEM teaching modules at Asparaga Seniro High School, Gorontalo, to equip teachers with more inclusive and adaptive teaching strategies. The methods used in this activity include training, mentoring, and evaluation based on surveys and direct observations. The results of the activity indicate an improvement in teachers' understanding of STEM and differentiation concepts, as well as their success in designing and implementing teaching modules tailored to students' needs. The evaluation also reveals that the application of ethno-STEM, which integrates local culture into STEM learning, enhances student engagement and makes learning more contextual and meaningful. Thus, the dissemination of this differentiated STEM-based teaching module contributes to the transformation of learning into a more innovative and relevant approach that meets the needs of 21st-century education.